How to get your PhD in Three Years : Real Experience via Thesis Publication - Rosmaini Tasmin; Muhamad Saufi Che Rusuli; Aliyu Abu Bakar; Abubakar Sadiq; Ishaq Jaafar (Penerbit UTHM, 2020)
This book is crafted to depict a general understanding on what it takes to venture into the PhP journey. The work is deemed important as many PhD candidates, starting PhD studies without having good knowledge of what lay ahead of his/her 3 years of studies. Having stated that, at least, this book will give good initial understanding and overview what candidates will encounter; since it is written based on true experience of a PhD supervisor and his many graduated candidates. The niche of this book on earning your PhD in 3 years, is primarily structured based on the three-staged years of the scholar pursuance and its emphasis on writing PhD thesis via many publications. List of publications, meanwhile pursuing PhD, is vital in creating leverage and confidence the fact that the presented thesis work has undergone a substantial process of review, commenting, correction and enhancement. By reading this book, readers will be exposed to ups and downs, do’s and don’ts and expecting they will enjoy the scholarly journey. Hopefully, this book will be able to show how to do it right at the first time and how valuable the experience of earning a PhD qualification.